Status of soil microbial population, enzymatic activity and biomass of selected natural, secondary and rehabilitated forests - Karam Singh, Daljit Singh; Abdu, Arifin; Othman, Radziah; Jusop, Shamshuddin; Abdul Hamid, Hazandy; Nik Ab. Majid, Nik Muhamad; Jamaluddin, Aiza Shaliha; Rui, T. X.; Keeren, S. R. (Science Publications, 2013)
Substantial clearance of forests and conversion of forest into various land use types contribute to deterioration of soil fertility and associated nutrients loss. Soils from natural and rehabilitated forest in Chikus Forest Reserve and also enrichment planting forest and secondary forest of Tapah Hill Forest Reserve, Perak, Malaysia were selected in order to assess the influence of land use change on biological properties. This study was carried out to provide fundamental information on soil biological properties and also to compare the differences between natural forest, mono-rehabilitated forest, mixed planting forest and natural regenerated forest (secondary forest). Six subplots (20×20 m) were established at each study plot and soil samples were collected at the depths of 0-15 cm (topsoil) and 15-30 cm (subsoil). Soil microbial population was determined using spread-plate technique. Fluorescein Diacetate (FDA) hydrolysis was used to assess the amount of microbial enzymatic activity for each forest plot. Soil Microbial Biomass C (MBC) and N (MBN) were extracted using chloroform fumigation extraction technique and the amount of MBC was determined by dichromate digestion, while MBN via Kjeldahl digestion technique. Soil acidity was determined by pH meter and moisture content was elucidated using gravimetric method. The levels of microbial population of bacterial and fungal at natural significantly exceeded the corresponding values of rehabilitated and secondary forest. However, microbial population is much higher in rehabilitated forest of Tapah Hill compared to that of secondary forest and also Chikus Forest Reserve planted forest which proves that rehabilitation activities do help increase the level of microbial community in the soils. Longer period of time after planting as in enrichment planting compared to mono planting of S. leprosula plantation showed that restoring and recovery of the planted forest needed time. Deforestation activities decrease soil biological activities; however, proper forest management and rehabilitation activities are able to restore the condition of degraded forest land to its original state.